Development Of Thinking Abilities In Preschool Children - Abitkhan Sabitkhanovich Shakirov (Euro Asian Journal Publishing, 2024)
The subject of the article. The article highlights issues related to the perception of the environment in preschool children. The naturalness of the coverage of this issue is related to the exclusive responsibility of the parents and the closest relatives of the baby. It is at this age that the basic sensual, moral and physical qualities are formed, which subsequently form the main moral, ethical and psychological foundation of the future person. But it should be noted that the ability of an adequate and creative level of thinking instilled in infancy is directly related to the process of high-quality and productive education in schools.
Keywords: preschool age; thinking; interpersonal relationships